2013
DOI: 10.3109/13625187.2013.792637
|View full text |Cite
|
Sign up to set email alerts
|

Statement on combined hormonal contraceptives containing third- or fourth-generation progestogens or cyproterone acetate, and the associated risk of thromboembolism

Abstract: TitleStatement on combined hormonal contraceptives containing third-or fourth-generation progestogens or cyproterone acetate, and the associated risk of thromboembolism. Permalinkhttps://escholarship.org/uc/item/2g26x0v0 JournalThe journal of family planning and reproductive health care, 39(3)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
5

Year Published

2013
2013
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 25 publications
0
4
0
5
Order By: Relevance
“…20 Based on a relative risk of 2, the excess risk of death for a woman taking modern combined hormonal contraceptives is 1 in 100 000, which is much lower than the risk of everyday activities such as cycling. 23 There is also conflicting evidence regarding whether the transdermal route of administration is associated with a higher incidence of venous thromboembolism. Several studies have indicated a 2-fold increase among patch users 24 while others have not confirmed this.…”
Section: Discussionmentioning
confidence: 99%
“…20 Based on a relative risk of 2, the excess risk of death for a woman taking modern combined hormonal contraceptives is 1 in 100 000, which is much lower than the risk of everyday activities such as cycling. 23 There is also conflicting evidence regarding whether the transdermal route of administration is associated with a higher incidence of venous thromboembolism. Several studies have indicated a 2-fold increase among patch users 24 while others have not confirmed this.…”
Section: Discussionmentioning
confidence: 99%
“…Доведено, що в пацієнток із СПКЯ ризик венозних тром-боемболічних ускладнень є значно вищим, ніж загалом у популяції [54][55][56]. Так, у масштабному дослідженні за участю 90 тис.…”
Section: інструментальні обстеженняunclassified
“…Однако следует помнить, что риск венозной тромбоэмболии при приеме этих препаратов в целом невысок и гораздо ниже такового во время беремен-ности и в ранний послеродовой период [8].…”
Section: табл 2)unclassified